2008
DOI: 10.1177/039463200802100209
|View full text |Cite
|
Sign up to set email alerts
|

Non-Allergic Rhinitis with Eosinophils and Mast Cells Constitutes a New Severe Nasal Disorder

Abstract: In this review we describe the relation between nasal eosinophilia and rheumatoid arthritis (RA). Moreover we was performed a literature revision that valued the relation between eosinophilia in respiratory system with arthritis. We have examined, through nasal cytology, 7 patients (5 men and 2 women) aged between 7 and 60 years old, with a middle age of 38,5 years; this patients are affected by RA, members of UO of Diagnostic ORL and nasal cytology of the AIAS (Italian Association of Disadvantages assistance)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 16 publications
3
63
0
5
Order By: Relevance
“…In the present study, we show that stimulation of SCCs triggers a proinflammatory pathway reflecting common features with idiopathic NAR (11,(48)(49)(50). Patients with NAR, similar to patients afflicted with asthma or chronic obstructive pulmonary disease (COPD), report hyperresponsiveness to normally benign odorants (51), including many chemicals that activate SCCs (52).…”
Section: Related To Nonallergic Rhinitis (Nar)mentioning
confidence: 74%
“…In the present study, we show that stimulation of SCCs triggers a proinflammatory pathway reflecting common features with idiopathic NAR (11,(48)(49)(50). Patients with NAR, similar to patients afflicted with asthma or chronic obstructive pulmonary disease (COPD), report hyperresponsiveness to normally benign odorants (51), including many chemicals that activate SCCs (52).…”
Section: Related To Nonallergic Rhinitis (Nar)mentioning
confidence: 74%
“…Although it is controversial on how to best subdivide NAR, several studies have recently demonstrated that a cytological approach may be useful not only to establish involvement of inflammation, but also to improve classification (19)(20)(21) . There is debate regarding the role of inflammation in NAR.…”
Section: Introductionmentioning
confidence: 99%
“…Findings also support the view that neuro-immune abnormalities occur in the brain of autistic patients and may contribute to the diversity of the autistic phenotypes (4). Although several lines of research support the view that this is a result of a complex combination of neurological, environmental, immunological, and genetic factors, it is widely reported that several white blood cells are important in the pathogenesis of neurological diseases (5)(6)(7)(8), and it is established in animal and human diseases such as autoimmunity, inflammation and cancer (9)(10)(11)(12)(13)(14). In addition, proinflammatory cytokines secreted by different types of cells contribute to the pathogenesis ofneuro-inflammation (12,15).…”
mentioning
confidence: 99%